A Critical Essay on Black Male Teacher Recruitment Discourse. Issue 5 (19th October 2020) - Brown, Anthony L.; Thomas, Daniel J.
ABSTRACT: Drawing from the framework of  populational reasoning, this paper explores the implicit and explicit discourses within recruitment calls for Black male teachers.  Populational reasoning  helps to construct meaning about how students learn and the socio-psychological attributes that inform school achievement. In this sense, we are interested in how wider discourses about Black male youth are tied to longstanding histories about the sociology of the Black family, which inform recruitment discussions about Black male teachers.